Газомасляный кожухотрубный теплообменник с безопасным каналом в маслосистеме газотурбинного двигателя газоперекачивающего агрегата - Смирнов, Андрей Витальевич; Середа, Роман Николаевич; Борисов, Николай Анатольевич (НТУ "ХПИ", 2016)
Рассмотрено два варианта подогрева топливного газа газотурбинного двигателя ГПА с использованием подогревателя топливного газа огневого типа и кожухотрубного газомасляного теплообменника с безопасным каналом. Представлена методика исследования и выполнен экономический анализ рассмотренных схемных вариантов по подогреву топливного газа. Экономически обосновано применение кожухотрубного газомасляного теплообменника с безопасным каналом в маслосистеме газотурбинного двигателя ГПА.

To design the equipment for chemical and petrochemical industry, power units, etc. economic indexes are selected as the efficiency criterion especially in conditions of severe competition on the market. The economic indexes are the most informative, because these take into consideration the sphere of production and the sphere of operation. The purpose of this scientific paper is to determine the economic efficiency of the use of gas-oil shell-and-tube heat exchanger with the safe channel in the oil system of gas turbine engine for the gas-compressor unit.
Gaseous oil shell-and-tube heat exchanger with the safe channel in the oil system of gas turbine engine for the gas-compressor unit
Keywords: биметаллическая ребристая труба; подогрев топливного газа; приведенные затраты; экономический эффект; bimetal riffled tube; fuel gas heating